Bovine Immunoglobulin E Levels of Bali Cattlesin Bangli and Nusa Penida island Bali Province, Indonesia - Suwiti, Ni Ketut; Heryani, Luh Gde Surya; Laksmi, Desak Nyoman Dewi Indira; Susari, Ni Nyoman Werdi; Besung, I Nengah Kerta; Besung, I Nengah Kerta (Journal of Veterinary and Animal Sciences, 2019)
The aim of this research was to detect identify levels of Bovine Immunoglobulin E (BoIg.E), can be used as an indicator of response immune in bali cattle.  Eighty serum samples were collected from Nusa Penida and Bangli region. Bovine Ig.E levels was measured using a commercial Enzyme Linked Immunosorbent Assay (ELISA) Kit. The data were analysis based on differences of farming characteristics andgeographic. The result of research that, of BoIg.E level of bali cattle kept in Bangli (34.16258 ?g/ml), was higher than Nusa Penida (22.26047 ?g/ml). We conclude that there was a significant effect of differences of farming characteristics and geographic conditions.